2013
DOI: 10.3402/gha.v6i0.19244
|View full text |Cite
|
Sign up to set email alerts
|

The non-fatal disease burden caused by type 2 diabetes in South Africa, 2009

Abstract: BackgroundIncreasing urbanisation and rising unhealthy lifestyle risk factors are contributing to a growing diabetes epidemic in South Africa. In 2000, a study estimated diabetes prevalence to be 5.5% in those aged over 30. Accurate, up-to-date information on the epidemiology and burden of disease due to diabetes and its sequelae is essential in the planning of health services for diabetes management.ObjectiveTo calculate the non-fatal burden of disease in Years Lost due to Disability (YLD) due to diabetes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
71
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 29 publications
1
71
0
Order By: Relevance
“…20 A recent study reported the prevalence of DM (age standardised) to be about 20% amongst Indians living in a suburb near Durban. 21 Despite a high prevalence amongst Indian patients, the current trend in South Africa is an increase of T2DM in the urban-based, Black South Africans and a much earlier diagnosis, 6 which is a new phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 A recent study reported the prevalence of DM (age standardised) to be about 20% amongst Indians living in a suburb near Durban. 21 Despite a high prevalence amongst Indian patients, the current trend in South Africa is an increase of T2DM in the urban-based, Black South Africans and a much earlier diagnosis, 6 which is a new phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…4 A recent study showed the prevalence of T2DM amongst South Africans above 30 years of age to be at around 9%, with 7.4% in men and 10.4% in women. 6 Blood glucose monitoring is important in optimising long-term outcomes towards reducing the co-morbid conditions that may arise in patients with T2DM. There is strong epidemiological evidence to use glycated haemoglobin (HbA1c) <7% as the target level and patients with T2DM with an HbA1c level of > 7.5% have a 2.5 to 5-fold greater relative risk of developing microvascular complications.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 The prevalence study by Bertram et al reported a potential rise in type 2 diabetes mellitus in South Africa from 5.5% in 2000 to 9% in 2009 in people aged 30 or older since the previous approximations. 9 Secondary studies by Bertram et al furthermore revealed that in South Africa around 55% of cases remained undiagnosed. 9 In a cross-sectional survey of 642 participants aged ≥ 31 years from an urban South African coloured community in Bellville South, Cape Town, T2DM was evaluated using the World Health Organization (WHO) criteria.…”
Section: Introductionmentioning
confidence: 99%
“…[1] It is of concern that about 55% of people with diabetes are likely to suffer from diabetic retinopathy. [2] Diabetes is the third leading cause of blindness in SA, with retinopathy and cataracts [2] accounting for 8 000 new cases of vision impairment every year. In a 2010 survey in Cape Town, diabetic retinopathy was responsible for 8% of blindness and 11% of severe visual impairment.…”
mentioning
confidence: 99%
“…[3] In LMICs, including SA, diabetic blindness creates a poverty cycle that disables breadwinners and burdens caregivers. The fact that timely treatment of diabetic retinopathy can reduce the risk of visual impairment by 90% [2] implies a need for screening and early detection. The Ophthalmology Society of South Africa has recommended a strategy for diabetic retinopathy screening using a validated grading system, an internet-based database and tracking system, and a patient-held 'scorecard' .…”
mentioning
confidence: 99%